2020
DOI: 10.3390/ani10020279
|View full text |Cite
|
Sign up to set email alerts
|

Application of Campylobacter jejuni Phages: Challenges and Perspectives

Abstract: Bacteriophages (phages) are the most abundant and diverse biological entities in the biosphere. Due to the rise of multi-drug resistant bacterial strains during the past decade, phages are currently experiencing a renewed interest. Bacteriophages and their derivatives are being actively researched for their potential in the medical and biotechnology fields. Phage applications targeting pathogenic food-borne bacteria are currently being utilized for decontamination and therapy of live farm animals and as a bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…Such population dynamics could consequently affect the use of Fletchervirus phages in broiler farms, which has been proposed as a promising intervention strategy to reduce Campylobacter loads before slaughter (Jane z and Loc-Carrillo, 2013). So far, studies of phage therapy that targets Campylobacter in chickens and at farm level have demonstrated varying efficiencies and phage-resistance development (Carvalho et al, 2010;Chinivasagam et al, 2020;Fischer et al, 2013;Ushanov et al, 2020). However, most of the phages used in these studies are not well characterized with respect to their receptors, and they have also not been sequenced.…”
Section: Accessmentioning
confidence: 99%
“…Such population dynamics could consequently affect the use of Fletchervirus phages in broiler farms, which has been proposed as a promising intervention strategy to reduce Campylobacter loads before slaughter (Jane z and Loc-Carrillo, 2013). So far, studies of phage therapy that targets Campylobacter in chickens and at farm level have demonstrated varying efficiencies and phage-resistance development (Carvalho et al, 2010;Chinivasagam et al, 2020;Fischer et al, 2013;Ushanov et al, 2020). However, most of the phages used in these studies are not well characterized with respect to their receptors, and they have also not been sequenced.…”
Section: Accessmentioning
confidence: 99%
“…Therapeutic use of phages is an approach employed in control of many foodborne bacteria, including Campylobacter, in the food production chain [ 32 , 33 , 34 ]. Phage therapy is also considered an alternative treatment method in the fight against antibiotic-resistant bacterial strains [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of fosfomycin for each clinical strain was determined using the agar dilution method, wherein the media were supplemented with glucose-6-phosphate (25 mg/L), according to the recommendations of the Clinical and Laboratory Standards Institute [CLSI], 2018 ( Ushanov et al, 2020 ). The data were interpreted according to the European Committee on Antimicrobial Susceptibility Testing criteria (available at http://www.eucast.org/clinical_breakpoints/ ) (susceptible, ≤32 mg/L; resistant, ≥64 mg/L), and the fosfomycin-resistant isolates were selected for further investigation.…”
Section: Methodsmentioning
confidence: 99%